2019
DOI: 10.1038/s41598-019-38609-4
|View full text |Cite
|
Sign up to set email alerts
|

Reduced mitochondrial respiration and increased calcium deposits in the EDL muscle, but not in soleus, from 12-week-old dystrophic mdx mice

Abstract: Mitochondria play an important role in providing ATP for muscle contraction. Muscle physiology is compromised in Duchenne muscular dystrophy (DMD) and several studies have shown the involvement of bioenergetics. In this work we investigated the mitochondrial physiology in fibers from fast-twitch muscle (EDL) and slow-twitch muscle (soleus) in the mdx mouse model for DMD and in control C57BL/10J mice. In our study, multiple mitochondrial respiratory parameters were investigated in permeabilized muscle fibers fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 45 publications
(58 reference statements)
1
10
0
Order By: Relevance
“…To our knowledge, this work represents the first to suggest that mitochondrial ultrastructure is impacted prior to muscle fiber damage. We further observed impaired complex IV enzymatic activity as previously described (Gaglianone et al, 2019). While not extensively tested, published research does suggest a mitochondrial phenotype occurring early in muscular dystrophy disease progression (Nghiem et al, 2017;Vila et al, 2017;Barker et al, 2018).…”
Section: Discussionsupporting
confidence: 83%
“…To our knowledge, this work represents the first to suggest that mitochondrial ultrastructure is impacted prior to muscle fiber damage. We further observed impaired complex IV enzymatic activity as previously described (Gaglianone et al, 2019). While not extensively tested, published research does suggest a mitochondrial phenotype occurring early in muscular dystrophy disease progression (Nghiem et al, 2017;Vila et al, 2017;Barker et al, 2018).…”
Section: Discussionsupporting
confidence: 83%
“…DMD pathogenesis is multifaceted and only partially understood. We and others have documented mitochondrial dysfunction [ 19 , 62 , 68 , 69 ] and oxidative stress [ 17 , 19 , [70] , [71] , [72] ] as central features of the disease. Specifically, we discovered that a mitochondrial Complex I deficit was implicit in the cascade leading to energy depletion, which could be partially recovered by re-routing metabolic flux through Complex II (and chemically inhibiting Complex I) [ 62 ].…”
Section: Duchenne Muscular Dystrophy: When Ros Become Foesmentioning
confidence: 99%
“…Others have reported similar mitochondrial aberrations [ 20 , 73 , 74 ] culminating in energy production deficits [ 62 , 73 ], which may influence the capacity of the muscle to mitigate damage and initiate repair since these processes are energetically-expensive. Furthermore, dysfunctional dystrophic mitochondria generate toxic amounts of ROS [ 17 , 19 , 62 , 68 , 69 , 75 ] resulting in protein and lipid damage via elevated 4-hydroxynonenal (4-HNE) [ 76 ], peroxynitrite [ 75 ], and oxidative [ 17 ] and nitrosative stress [ 75 ], all of which drive the dystrophic condition. Despite dystrophic muscle – from human patients and the genetically homologous mdx mouse model – expressing higher levels of antioxidants including SOD and CAT during peak muscle damage periods [ [77] , [78] , [79] ], overall antioxidant capacity appears to be insufficient to mitigate ROS as evidenced by lipid [ 80 ] and protein [ 81 ] peroxidation and hypersecretion of pro-inflammatory cytokines [ 22 , 82 ].…”
Section: Duchenne Muscular Dystrophy: When Ros Become Foesmentioning
confidence: 99%
“…Muscles of DMD patients and mouse models of dystrophy have impaired oxidative phosphorylation and mitochondrial function [ [9] , [10] , [11] ], which contribute to the disease etiology. Chronic low-frequency electrical stimulation (LFS) has improved understanding of the adaptive and metabolic plasticity of skeletal muscle [ 12 , 13 ], and in preliminary trials, this approach has shown potential for improving muscle strength in DMD patients [ [14] , [15] , [16] , [17] ] and in mouse models of muscular dystrophy [ [18] , [19] , [20] ].…”
Section: Introductionmentioning
confidence: 99%